Evaluasi Keberhasilan Sistem Informasi Akademik dengan Pendekatan Model DeLone dan McLean - Meilani, Lala; Suroso, Arif Imam; Yuliati, Lilik Noor (Universitas Diponegoro, 2020)
Development of academic management needs will increasingly complex, therefore the development of academic information systems must be oriented to user satisfaction as a way to measure the success of the information system. This study aims to analyze the performance of the quality of academic information systems (SIAKAD) and analyze the factors that influence the use, user satisfaction and net benefits of SIAKAD at Sultan Ageng Tirtayasa University. The respondents used in this study consisted of three groups totaling 400 people. The model used in this research is the information system success model from DeLone and McLean. Descriptive analysis is used to explain respondents' perceptions and evaluations of the successful implementation of SIAKAD. SEM PLS analysis is used to analyze the factors that influence the successful implementation of SIAKAD at Sultan Ageng Tirtayasa University. SIAKAD users rated success at the semantic level and technical level included in the good category, while the success at the effectiveness level was still in the good enough category. Hypothesis testing results indicate that the quality of information system quality and service quality has a significant positive effect on the use and satisfaction of users, the use of a significant positive effect on user satisfaction, and the use and satisfaction of users has a positive and significant effect on the net benefits of SIAKAD.